Understanding older adults’ adherence to the consumption of products provided by the Supplementary Food Program for Older Adults (PACAM ) by exploring the point of view of users from the municipality of Hualpén, Chile - Parra-Muñoz, Estefanía; Ortega-Senet, María Belén (Revista Chilena de Salud Pública, 2019)
Introduction. The Supplementary Food Program for Older Adults (known by the acronym PACAM) is a Chilean program aimed at preventing and/or supporting elderly individuals’ recovery from malnutrition. Poor adherence to PACAM in recent years motivates this study. Objectives. To understand the reasons for the low adherence of older adults to the consumption of PACAM products (milk drink and a fortified powdered soup known as “Golden Years Cream”), in order to propose alternatives for improving the program based on the interests and preferences of elderly users. Methods. A qualitative study, with a phenomenological and hermeneutical approach, was conducted, focused on interpreting the meaning of the users’ subjective experiences. The study, which was carried out during the first semester of 2017, consisted of 20 semi-structured interviews conducted with older adults of both sexes, who were beneficiaries of PACAM in the Chilean municipality of Hualpén. Results and conclusions: Food odor, taste, consistency, preparation, and quantity were some of the organoleptic properties identified by the subjects, while the external factors included quality of life, social networks, the influence of other users, relationships with professionals in the health centers, daily life, and habits.